Design methodology for the development of variable stiffness devices based on layer jamming transition. (30th August 2021) - Arleo, Luca; Bondì, Giorgio; Albini, Stefano; Maselli, Martina; Cianchetti, Matteo
Abstract: Variable stiffness mechanisms as Jamming Transition draw huge attention recently in Soft Robotics. This paper proposes a comprehensive design methodology for developing variable stiffness devices based on layer jamming. Starting from pre-existing modelling, we highlight the design parameters that should be considered, extracting them from literature and our direct experience with the phenomenon. Then we validated the methodology applying the design process to previous layer jamming cases presented in literature. The comparison between the results obtained from our methodology and those presented in the analyzed previous works highlights a good predictive capability, demonstrating that this methodology can be used as a valid tool to design variable stiffness devices based on layer jamming transition. Finally, in order to provide the scientific community with an easily usable tool to design variable stiffness structures based on layer jamming transition, we have elaborated a Matlab script that guides the user through the main design parameters implementing the proposed methodology in an interactive process.